Determination of the embryonic axes of Drosophila. - Nusslein-Volhard, C. (Molecular and cellular basis of pattern formation., 1991)
The principles of embryonic pattern formation have been studied extensively in many systems using classical experimental approaches. In Drosophila, a powerful combination of genetics and transplantation experiments, as well as molecular biology, have helped to elucidate the mechanisms that operate during oogenesis and early embryogenesis to establish a set of positional cues required for axis determination in the early embryo. In systematic searches for maternal effect mutations a small number of about 30 genes have been identified that specifically affect the process of determination of the embryonic axes. These 'coordinate' genes define four systems that determine the anteroposterior (AP) axis (three systems) and the dorsoventral (DV) axis (one system) independently. In the anteroposterior axis, the anterior system determines the segmented region of head and thorax, the posterior system determines the segmented abdominal region, and the terminal system is responsible for the formation of the nonsegmented termini at the anterior and posterior egg tips, the acron and telson. In contrast, pattern along the dorsoventral axis is determined by one system only. Although all four systems use different biochemical mechanisms, they share several properties. (1) The product of one gene in each system is localized in a specific region of the freshly laid egg and functions as a spatial signal. (2) In each system, this spatial information finally results in the asymmetrical distribution of one gene product that functions as a transcription factor. (3) This transcription factor is distributed in a concentration gradient that defines the spatial limits of expression of one or more zygotic target genes. The combined action of these three anteroposterior systems as well as the dorsoventral system defines the expression of zygotic target genes in at least seven distinct regions along the anteroposterior and at least three in the dorsoventral axis. These longitudinal and transverse domains provide a coarse spatial prepattern which is then further refined by the action and interaction of zygotic pattern genes.